Extraction, derivatization, and determination of metabolome in human macrophages. Issue 8 (22nd March 2013) - Cheng, Jianhua; Che, Nanying; Li, Haijing; Ma, Kunpeng; Wu, Shengming; Fang, Junjian; Gao, Rong; Liu, Jiexin; Yan, Xianzhong; Li, Chuanyou; Dong, Fangting
<x xml:space="preserve">Abstract</x> A GC/TOF‐MS was applied to the determination of metabolites in human macrophages. The extraction conditions and quenching conditions were investigated and optimized. The results indicated that 0.9% w/v sodium chloride at 4°C was the most favorable condition to quench macrophage, 1 mL 50% ACN for 2 min in ice bath was the optimal condition to extract 5 × 106 cells. Two hundred six peaks could be detectable with peak area over 50 using this method. Among these peaks, 45 peaks with the similarity over 700 were identified using standard compounds for endogenous metabolites. Thirty‐seven out of 45 metabolites could be quantified directly by this method. Twenty metabolites were selected randomly, and 15 amino acids were used for method validation. The correlation coefficients (r) ranging from 0.9902 to 0.9977 were obtained for 15 amino acids in the range of 2.35–150.20 μg/mL. The intraday and interday precisions were lower than 19.90% for the randomly selected 20 endogenous metabolites. Using this development method and multivariate statistical technique, several potential biomarkers were found from human macrophages infected by different Mycobacterium tuberculosis (M. tuberculosis) strains. The results suggest that the method could be applied to the investigation of the pathogenicity of tuberculosis.